Análise paleopalinológica do Albiano (Cretáceo inferior) da Bacia de Campos, com ênfase no estudo de dinoflagelados - Nascimento, Clara Rodrigues [UNESP] (2015)
The present work has aimed to provide an inventory of marine and continental palynomorphs from the Campos Basin; and to analyse their distribution within the sampled sections in order to evaluate paleoenvironmental and paleobiogeographic models. Lower Cretaceous (Albian) palynomorphs from the Macaé Group, as intersected in the Bonito and Pampo wells, constitute the basis of this study. Gymnospermous pollen grains occur in notable abundance, especially Classopolis classoides, Gnetaceapollenites sp. and Equisetosporites sp., which are typically xeromorphic. The most abundant dinoflagellates are the cosmopolitan species Spiniferites ramosus, Odontochitina operculata and Trichodinium castanea. Four typically Tethyan dinoflagellate species identified are Codoniella campanulata, Cyclonephelium vannophorum, Endoceratium dettmanniae and Tehamadinium mazaganense. The proportion of land-derived palynomorphs in the strata (mainly spores, pollen grains and plant debris) increases at the end of the Albian, concomitant with the transition from carbonates to shales and marls. Furthermore, marine palynomorphs increase in diversity from the base to the top of the studied sections, changing from a biota dominated by palynoforaminifera to one rich in dinoflagellates. Integration of the micropaleontological data indicates that, during the establishment of the South Atlantic Ocean, the Campos Basin received water from the Tethys Ocean. This refutes the classic model that invokes the incursion of Austral water accompanying the tectonic opening from south to north